UNEP Year Book 2013: emerging issues in our global environment - United Nations Environment Programme (UNEP, 2016)
The UNEP Year Book 2013 shows that changes in the Arctic will have consequences far beyond this fragile region and that they require an urgent international response. The volume of chemicals in the world continues to grow, with a shift in production from developed to developing countries. To meet the goal of producing and using chemicals in ways that minimize significant impacts on health and the environment by 2020, we need to step up efforts to reduce the use of toxic chemicals, promote safer alternatives and build capacity for sound chemicals management. Adequate information for minimizing chemical risks is essential to support these efforts. The UNEP Year Book series examines emerging environmental issues and policy-relevant events and developments.